US-Iran relations embracing a new realism - Monshipouri, Mahmood 1952- (Emirates lecture series, 2009)
This paper's main thrust is to make a case for direct diplomacy with Iran, while explaining factors that have contributed to the end of "coercive diplomacy" advocated by the Bush administration. The premise underlining this paper is that there has never been a stronger case for the normalization of relations between Iran and the United States in a region fraught with difficulties and crises. Iran's stabilizing influencing in the region inevitably has enhanced its role in shaping the region's geopolitics. Iran's influence in Afghanistan can no longer be marginalized, nor can its role be underestimated in the southern parts of Iraq and Lebanon, as well as its ties with Hamas and Syria." Publisher's Website